Analyst Forecast Accuracy and Media Independence. Issue 4 (12th May 2017) - Kim, Jeong‐Bon; Li, Liuchuang; Zhang, Hao
Abstract: Using a large international sample of 47, 307 firm‐years from 52 countries, we investigate the impact of media independence on the forecast quality of financial analysts. We find that analyst forecast errors are positively associated with the extent of a country's state media ownership and its lack of freedom of the press. We also find that financial analysts with more inaccurate forecasts disappear from the institutional broker's estimate system more quickly in countries with more independent media.